THE EFFECT OF KINGCO PERFUME PRODUCT QUALITY AND PRICE ON CUSTOMER BUYING INTEREST - Syamsuri, Abd. Rasyid; Afriliani, Sri; Khairunilah, Dila (PT Aksara Indo Rajawali, 2022)
This study aims to analyze the quality and price of KingCo Perfume products on customer buying interest in the Dusun V Community, Patumbak District, Deli Serdang Regency, North Sumatra. This is a descriptive quantitative study that employs observation, interviews, and questionnaires to collect data. The sample size for this study was 37 customers. The sampling strategy employed in this study was saturation sampling, which entails taking a sample from the entire population. Multiple linear regression with the SPSS program was used to conduct the research analysis. With a significant value of 0.002, the partial test results demonstrate that the quality (X1) has a t-count value (3.356) > the t-table value (2.034), indicating that Ha is approved and Ho is refused. This shows that quality (X1) has a positive and significant impact on purchasing interest (Y). With a significant value of 0.005, Price (X2) has a t-count value (2.966) > t-table value (2.034), indicating that Ha is accepted and Ho is rejected. The findings of this study show that price has a positive and significant effect on purchasing interest (Y). The f count value is 29.342> f table 2.88 with a sig value of,000 < 0.05, according to the findings of the simultaneous test. The results of this statistical test show that in Dusun V, Patumbak District, Deli Serdang Regency, North Sumatra, Quality (X1) and Price (X2) has a positive and significant effect on customers' Buying Interest (Y).